The relationship between social support, coping strategies and stress among Iranian adolescents living in Malaysia - Rabbani, Mohtaram; Mansor, Mariani; Yaacob, Siti Nor; Abu Talib, Mansor (Sakarya University, Faculty of Education, 2014)
The major purpose of this study is to investigate the relationship between social support, coping strategies and stress among 150 Iranian adolescents among Iranian adolescents in Malaysia. Child and Adolescent Social Support Scale, the Adolescent Stress Questionnaire and Brief COPE Inventory, which evaluate the various ways people react to stress were employed in this study. The Sobel Mediation Test was conducted to examine the mediation outcome of problem-focused coping strategies on the relationship of social support and stress with insignificant results. Therefore, social support does not significantly impact stress through problem-focused coping strategies (z = 0.57, p > 0.05). The Sobel Mediation Test was also conducted to determine the mediation impact of emotion-focused coping strategies on the relationship between social support and stress is significant. So, social support significantly affect stress through emotion-focused coping strategies (z = 2.29, p < 0.05). The results of this investigation indicated that problem-focused coping strategies cannot mediate the relationship between social support and stress, but emotion-focused coping strategies can. Additional to the general inverse relationship between social support and stress, the use of emotion-focused coping strategies serves to strengthen the effect of social support with stress. In particular, with increase in stress, students using emotion-focused coping strategies tend to have less stress. This suggests that emotion-focused coping strategies are effective strategies to bring about decreased stress among adolescents. This study confirms the belief that using emotion-focused coping strategies could have a correlation with lower stress among Iranian adolescents and can mediate the relationship between social support and stress.